Technical Feasibility and Histological Analysis of Balloon-Expandable Metallic Stent Placement in a Porcine Eustachian Tube - Yehree Kim; Woo Seok Kang; Jeon Min Kang; Dae Sung Ryu; Min Young Kwak; Ho-Young Song; Jung-Hoon Park; Hong Ju Park (Applied Sciences, 2021)
There is a clinical need to develop a stent to treat obstructive and refractory Eustachian tube dysfunction (ETD) after balloon Eustachian tuboplasty. An animal model for stent placement in the Eustachian tube (ET) is needed to develop optimal designs and materials, as stents for ETD have not been clinically applied. The purpose of this study was to evaluate the technical feasibility of stent placement and histological changes in a porcine ET model. Six ETs were evaluated in three pigs. Cobalt–chrome alloy stents with two different diameters were placed in the left and right ET of each animal (right, 3.5 mm; left, 2.5 mm). The outcomes were assessed by endoscopic and fluoroscopic imaging during the procedure, computed tomography after the procedure, and by histological examinations. Stent placement was technically successful in all specimens after metallic guiding sheaths were located in the nasopharyngeal end of the ET. The mean luminal diameters of the proximal, middle, and distal portions of the larger stents in the right ETs were 3.48 mm, 2.54 mm, and 2.15 mm, respectively. In the left ETs using smaller stents, these values were 2.49 mm, 1.73 mm, and 1.42 mm, respectively. The diameters of the inserted stents differed by stent location and the original diameter. Histological findings showed tissue hyperplasia with severe inflammatory cell infiltration at 4 weeks after stent placement. In conclusion, stent placement into the porcine ET was technically feasible, and stent-induced tissue hyperplasia was significantly evident. The luminal configuration of the placed ET stent changed according to its non-elastic nature and anatomical features of the porcine ET. Using this model, ET stents of various materials and designs with anti-inflammatory or anti-proliferative drugs can be optimized for future treatments of ET dysfunction.